Ginkgolide B Protects Against Ischemic Stroke Via Modulating Microglia Polarization in Mice. (16th June 2016) - Shu, Zhao‐Ma; Shu, Xiao‐Dong; Li, Hui‐Qin; Sun, Yi; Shan, Han; Sun, Xi‐Yang; Du, Ren‐Hong; Lu, Ming; Xiao, Ming; Ding, Jian‐Hua; Hu, Gang
Summary: Aim: Ginkgolide B (GB) has shown neuroprotective effect in treating ischemic stroke, related to its property of anti‐inflammation. Nevertheless, it is unclear whether GB is able to modulate microglia/macrophage polarization, which has recently been proven to be vital in the pathology of ischemic stroke. Methods: We performed transient middle cerebral artery occlusion (tMCAO) on C57BL/6J male mice and induced cultured BV2 microglia and primary bone marrow‐derived macrophages to be M1/2 phenotype by LPS+ interferon‐γ and IL‐4, respectively. Immunofluorescence and flow cytometry were used for detecting the specialized protein expression of M1/2, such as CD206 and CD16/32. qPCR was utilized to detect the signature gene change of M1/2. Results: GB significantly reduced cerebral ischemic damage and ameliorated the neurological deficits of mice after tMCAO. More importantly, our experiments proved that GB promoted microglia/macrophage transferring from inflammatory M1 phenotype to a protective, anti‐inflammatory M2 phenotype in vivo or vitro . CV3988 and silencing the platelet activator factor (PAF) receptor by siRNA demonstrated that PAF receptor was involved in the modulation of microglia/macrophage polarization. Conclusion: Our results reveal a novel pharmacological effect of GB in modulating microglia/macrophage polarization after tMCAO, thus deepening our understanding of neuroprotective mechanisms of GB in treatment of ischemic stroke. Furthermore, this new mechanism may allow GB to be used in many other microglia/macrophage polarization‐related inflammatory diseases.